2010
DOI: 10.1159/000251663
|View full text |Cite
|
Sign up to set email alerts
|

Colon Cancer Detection by ‘Rendezvous Colonoscopy’: Successful Removal of Stuck Colon Capsule by Conventional Colonoscopy

Abstract: Although capsule retention is a known complication of small bowel capsule endoscopy, initial studies with colon capsule endoscopy (CCE) have not reported any capsule retention or sticking neither in the small bowel nor in the colon. We report a complication of CCE when the stuck colon capsule was passed through the malignant colon stricture and removed by the aid of a flexible colonoscope. During CCE in a 76-year-old iron deficiency anemia patient the real-time viewing system indicated the colon capsule to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…The whole digestive tract barium meal cannot provide the entire view of the small intestine or obtain integrative imaging of the small intestine; as it sometimes can even induce intestinal obstruction, it can also be excluded from examination of diverticulum. Although it was reported that wireless capsule endoscopy is a useful diagnostic tool for diagnosing Meckel diverticulum, [ 23 , 24 ] the camera can sometimes become stuck in the intestine [ 25 , 26 ] and cause dangerous conditions [ 27 ] ; thus, wireless capsule endoscopy might not be the first choice for examining small intestinal diverticulum. [ 28 ] Compared with capsule endoscopy, double-balloon enteroscopy is reported to be a safer and more effective method; in addition, as it can be used to examine small intestinal diverticulum from both oral and anal directions and the small bowel completely, it can determine the specific location of the small intestinal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The whole digestive tract barium meal cannot provide the entire view of the small intestine or obtain integrative imaging of the small intestine; as it sometimes can even induce intestinal obstruction, it can also be excluded from examination of diverticulum. Although it was reported that wireless capsule endoscopy is a useful diagnostic tool for diagnosing Meckel diverticulum, [ 23 , 24 ] the camera can sometimes become stuck in the intestine [ 25 , 26 ] and cause dangerous conditions [ 27 ] ; thus, wireless capsule endoscopy might not be the first choice for examining small intestinal diverticulum. [ 28 ] Compared with capsule endoscopy, double-balloon enteroscopy is reported to be a safer and more effective method; in addition, as it can be used to examine small intestinal diverticulum from both oral and anal directions and the small bowel completely, it can determine the specific location of the small intestinal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the lifetime is enough to cover most patient's GI transit time [43,44]. However, an increased battery life may be useful for patients who need a longer GI transit time (capsule retention or other chronic disease) [45,46].…”
Section: Data Loggermentioning
confidence: 99%
“…Available studies with CCE, despite the larger capsule size, have not reported any capsule retention or sticking either in the small bowel or in the colon [7 -20]. Of note, a case of CCE where a stuck colonic capsule was passed through a malignant colonic stricture and removed with the aid of flexible colonoscopy has recently been reported [47]. Removal of colonic capsule retained in the small bowel may require surgery, although removal by device-assisted enteroscopy may be an option [45].…”
Section: Indications and Contraindications For Colon Capsule Endoscopmentioning
confidence: 99%